Sthreads: Multithreading for SCI clusters - Rehling, Enno (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.1999.19794, 1999)
Threads are in widespread use as a model for concurrent programming. In our effort to supply a broad range of tools for the SCI platform, we have created Sthreads, a library that simplifies the adaptation of programs written for the Pthreads library to SCI Cluster hardware. This paper presents the design decisions we made, and a performance evaluation comparing the Sthreads library to Pthreads.